Vocal Ornamentation Style of Sri Hartati in the Keroncong Song Bandar Jakarta by Iskandar - Suryati, Suryati; Legino, Rafeah; Artanto, Mei; Anugerah, Hafidz Akbar (Institut Seni Indonesia Yogyakarta, 2025)
Vocal ornamentation is very necessary for a singer. Vocal ornamentation can be applied to several genres of songs, one of which is keroncong songs. In performing keroncong songs, both Keroncong Asli, Langgam and Stambul have their own characteristic vocal ornamentation. Each singer also has their own characteristics in performing Keroncong songs. Therefore, this study focused on Sri Hartati's vocal ornamentation style in performing the Keroncong song